O centenário da independência do Brasil através dos jornais de Caxias do Sul e região - Schiochet, Gustavo Miglioranza (My University, 2022)
The present work aims to analyze the way in which the newspapers Città Di Caxias, La Staffetta Riograndense and O Brasil published in their pages the centenary of the independence of Brazil. The material analyzed, fully digitized, can be found in the historical archive of the newspapers of the Centro de Memória present on the website of the City Council of Caxias do Sul. First, the newspapers themselves were analyzed, investigating their trajectories to identify how they worked. Then, the context of the time of 1922 was presented, in which the newspapers were about to start analyzing their content. The first part of the content present in the newspapers directly refers to the centenary celebrations, not only in Caxias do Sul and region, but also in the Brazilian capital of the time Rio de Janeiro. Ending with the way the newspapers portrayed the independence process, identifying the presence of nationalist elements, main characters and moments according to the newspapers. [resumo fornecido pelo autor]
O presente trabalho tem como objetivo analisar a maneira com que os jornais Città Di Caxias, La Staffetta Riograndense e O Brasil divulgaram em suas páginas o centenário da independência do Brasil. O material analisado, totalmente digitalizado, encontra-se no acervo histórico dos jornais do Centro de Memória presente no site da Câmara de Vereadores de Caxias do Sul. Primeiramente foram analisados os próprios jornais, averiguando suas trajetórias para identificar como trabalhavam. Em seguida foi apresentado o contexto da época do ano de 1922 no qual os jornais estavam para somente então iniciar a análise de seu conteúdo. A primeira parte do conteúdo presente nos jornais se refere diretamente as celebrações do centenário, não somente em Caxias do Sul e região, mas também na capital brasileira da época Rio de Janeiro. Finalizando com a maneira como os jornais retrataram o processo de independência, identificando a presença de elementos nacionalistas, principais personagens e momentos segundo os jornais. [resumo fornecido pelo autor]
Keywords: Brasil - História - Independência, 1822; Jornais - Caxias do Sul (RS) - Análise; Nacionalismo